A Systematic Review of Culture-Based Guided Inquiry in Chemistry Education - Raudatul Hasanah Siregar; Isana Saupiah Yosephine Louise; Azlan Bin Kamari (Jurnal Pendidikan Sains Indonesia, 2026)
The implementation of culture-based guided inquiry in chemistry education has been widely reported to have a positive impact; however, systematic reviews that map the characteristics of its implementation and the direction of related research remain limited. This study aims to synthesize the implementation of culture-based guided inquiry in chemistry education through a systematic literature review (SLR). The study employed an SLR design in accordance with the PRISMA 2020 guidelines, based on the analysis of 19 articles published between 2016 and 2025 retrieved from scopus, ERIC, dimensions, and google scholar. Data were analyzed using thematic synthesis through primary and secondary coding processes. The results showed that the implementation of culture-based guided inquiry was dominated by the development of cognitive aspects, such as learning outcomes, chemistry literacy, critical thinking skills, and science process skills. Cultural integration was generally carried out through an ethnoscience approach by utilizing local culture and was supported by culture-based instructional materials, such as worksheets and e-modules. However, research on affective aspects remained limited, and no studies were found that specifically evaluated psychomotor skills as learning outcomes. This review highlights that culture-based guided inquiry supports more contextual and meaningful chemistry learning and provides opportunities for future research to integrate the evaluation of cognitive, affective, and psychomotor aspects in a more balanced manner